From noble Muslims to saracen enemies: Thomas Stamford Raffles’ discourse on Islam in the Malay world - Syed Muhd Khairudin Aljunied, (Universiti Kebangsaan Malaysia, 2003)
This article examines the development of Sir Thomas Stamford Raffles’ discourse on Islam as practised by the Malays. It is argued that this discourse shifted from admiration of Islam to the belief that it had brought detriment to the Malay World. Such a shift in discursive strategy, which denies the importance of Islam in the Malay World, was necessary due to several reasons. By denying the importance and contribution of Islam, Raffles and his compatriots left the Malay World open as potential missionary and colonisable territory. Also, by exaggerating the oppression and cruelty of systems preceding the arrival of the British, Raffles intended to publicise the success of his benevolent policies. Most importantly, in the narratives that follow, it will be demonstrated the ways Raffles make use of the influence of dominant ideologies and epistemologies in his milieu to denigrate Islam